Loom magic xtreme - McCann, John (Simon and Schuster London, 2014)
From the authors of the instant bestseller Loom Magic! comes a second amazing project book with twenty-five totally new and extreme designs! Rainbow Looms are taking the world by storm, with devotees of all ages accessorizing their wrists, backpacks, and rooms with fun and creative projects. These super imaginative, out-of-this-world projects will take your rubber band loom projects to the next level. Wow everyone around you with the Pirate Eye Patch, the Rainbow Unicorn, and the Loom Ninja! Here are step-by-step instructions and bright color photographs to show you how to m